A role for Waldeyer's ring in immunological response to allergens. (February 2014) - Masieri, Simonetta; Trabattoni, Daria; Incorvaia, Cristoforo; De Luca, Maria Cristina; Dell'Albani, Ilaria; Leo, Gualtiero; Frati, Franco
Abstract Objective: Adenoids, tubal tonsil, palatine tonsil, and lingual tonsil are immunological organs included in the Waldeyer's ring, the basic function of which is the antibody production to common environmental antigens. Adenoidal hypertrophy (AH) is a major medical issue in children, and adenoidectomy is still the most used treatment worldwide. The response of adenoids to allergens is a good model to evaluate their immunological function. This report assessed the immunological changes in adenoid tissues from children with allergic rhinitis (AR) undergoing sublingual immunotherapy (SLIT). Methods: Adenoid samples from 16 children (seven males, nine females, mean age 7.12 years) with AH and clinical indication to adenoidectomy were collected. Of them, five children were not allergic and 11 had house dust mite and grass pollen-induced AR. Among allergic children, in four AR was treated by antihistamines while in seven AR was treated by high-dose SLIT during 4–6 months. The evaluation addressed the T helper 1 (Th1), Th2, and Th3 cells by performing a PCR array on mRNA extracted from adenoid samples. Results: In non-allergic children, a typical Th1 pattern was found. SLIT induced a strong down-regulation of genes involved in Th2 and Th1 activation and function. In particular, in SLIT-treated allergic children IL-4, CCR2, CCR3, and PTGDR2 (Th2 related genes) and CD28, IL-2, and INHA (Th1 related genes) expression was reduced, compared with children treated with antihistamines. Conclusions: These preliminary findings warrant investigation in trials including larger numbers of patients, but indicate that hypertrophic adenoids of allergic children have the typical response to the specific allergen administered by SLIT. This should suggest that one should reconsider the immunological role of adenoids.